Phase I study of single‐agent ribociclib in Japanese patients with advanced solid tumors. Issue 1 (12th November 2017) - Doi, Toshihiko; Hewes, Becker; Kakizume, Tomoyuki; Tajima, Takeshi; Ishikawa, Norifumi; Yamada, Yasuhide
Abstract : The cyclin D‐CDK4/6‐INK4‐Rb pathway is frequently dysregulated in cancers. Ribociclib, an orally available, selective CDK4/6 inhibitor, showed preliminary clinical activity in a phase I study in the USA and Europe for patients with solid tumors and lymphomas. The present study aimed to determine the single‐agent maximum tolerated dose (MTD) and recommended dose for expansion (RDE) in Japanese patients with advanced solid tumors. Ribociclib safety, tolerability, pharmacokinetic profile, and preliminary antitumor activity were also assessed. Japanese patients with solid tumors that had progressed on prior therapies received escalating doses of single‐agent ribociclib on a 3‐weeks‐on/1‐week‐off schedule. Treatment continued until the development of toxicity or disease progression. A dose escalation was planned for patients with esophageal cancer. In the dose‐escalation phase, 4 patients received 400 mg ribociclib and 13 patients received 600 mg ribociclib. Four patients experienced dose‐limiting toxicities, 3 of whom were in the 600 mg group. The RDE was declared to be 600 mg, and the MTD was not determined. The most frequent adverse events were hematologic and gastrointestinal. Four patients achieved stable disease at the 600 mg dose; no patients achieved complete or partial response. All patients discontinued the study, the majority due to disease progression. No patients discontinued due to adverse events. Dose escalation was not pursued due to lack of observed efficacy in esophageal cancer. At the RDE of 600 mg/d on a 3‐weeks‐on/1‐week‐off schedule, ribociclib showed acceptable safety and tolerability profiles in Japanese patients with advanced solid tumors. Abstract : Our phase 1 study aimed to determine the maximum tolerated dose and recommended dose for expansion of single‐agent ribociclib in Japanese patients with Rb+ advanced solid tumors whose disease had progressed on prior therapy. Additionally, ribociclib safety, tolerability, pharmacokinetic profile, and preliminary antitumor activity were assessed. We found the RDE of single‐agent ribociclib to be 600 mg on a 3‐weeks‐on/1‐week‐off schedule. Single‐agent ribociclib exhibited an acceptable safety and tolerability profile with limited preliminary clinical activity. These findings were consistent with a phase 1 study of adult patients with solid tumors conducted in the United States and Europe.